RELATIONS BETWEEN RUSSIA AND TURKEY: THE PROSPECTS OF COLLABORATION - A. T. Mozloyev (Vestnik MGIMO-Universiteta)
The article examines the strategic analysis of the reasons and outcomes of the aggravation of the relations between Russia and Turkey after the catastrophe with the Russian military plane Su-24. The author outlines the most critical problems which have led to this tragic event using the philosophical approach. The article analyses the relations between the two countries from the strategic point of view on the assumption of the necessity to build up fruitful cooperation in the future. According to the author, purely economic factors because of which bilateral relations could be defined as strategic partnership, have proven to be insufficient when it has come to the political rapprochement of Russia and Turkey based on the commonly understood values of the regional cooperation amid the formation of the multipolar world. The author claims that Russia and Turkey could together become one of the poles using their regional cooperation in the regions of the Black sea and the Middle-East. Nevertheless, extra idealization of the two countries' rapprochement, taking into account the events of the 24th November, 2015, has caused political disenchantment with the perspective of taking the bilateral relations to the real level of strategic partnership which would include not only economic but other factors as well. The tragic event is not only about our plane being shut down but also about the murder of our soldiers what, also considering the reluctance of the Turkish elite to make apologies and its aspiration to postpone the normalization of the relations, makes it difficult to at least bring the relations back to their initial level.